Diodonopsis ramiromedinae (Orchidaceae: Pleurothallidinae), a new species from Colombia - Thoerle, Lisa; Medina Trejo, Ramiro (Lankesteriana: International Journal on Orchidology, 2017)
A new species, Diodonopsis ramiromedinae, is described, illustrated, and compared with similar species. A brief history of Masdevallia sect. Pygmaeae and the genus Diodonopsis is provided. Diodonopsis ramiromedinae is most similar to D. anachaeta, but differs by sepals with apices acute or acuminate-triangular vs. narrowly caudate; longer petals with a descending, narrowly linear, rounded basal process vs. with an acute, retrorse basal process; and the larger lip, obovate with the apex very broadly rounded vs. oblong-subpandurate with the apex acute.